Biofloc Technology as a Sustainable Alternative for Managing Aquaculture Wastewater (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
The rapid expansion of the aquaculture industry has resulted in a significant increase in wastes generated from fish farming systems, including undigested feed, recycled nitrogen, and other resources. Consequently, the rise in fish production has slowed, as aqua-preneurs are unable to achieve maximum output and profitability. Bio-floc technology (BFT) is a cutting-edge system with enormous potential for application in fish farming. BFT works on the premise of converting the solid waste generated from spilt or undigested feed by the fish or from feces in the form of solid and dissolved waste mainly carbon, nitrogen ammonium, and phosphorus to probiotic or nutritious protein for fish consumption. Using the technology, bacteria may convert bio-waste into edible nutrients for farm animals. Adoption of BFT can offer biosecurity measures that can limit the use of antibiotics and chemicals that have been outlawed by WHO/EU owing to rising environmental issues associated with their application. This study examines and presents BFT as a sustainable alternative for managing aquaculture wastewater and in-house provision of nutrients for cultured animals. The coverage of this study includes an overview of Aquaculture wastewater treatment, aquaculture wastewater as media for Biofloc formation, pathogens, probiotics, and potential for biofloc formation in aquaculture systems and BFT as a sustainable means of nutrition in aquaculture. The cost-effectiveness and potential of BFT in treating aquaculture wastewater are also critically discussed. The present study highlights the importance of harnessing BFT for cost-effective aquaculture production and alternative means of managing aquaculture wastewater.
Keywords: Aquaculture Waste Management; Bio-floc Technology (BFT); Sustainable Fish Farming; Nutrient Recycling in Aquaculture; Aquaculture Biosecurity